(untitled) (Academia Science Repository, 2023)
The formation of interest in the lesson is very important to increase the academic success and overall activity of elementary students. This article is aimed at studying various strategies that teachers can use to promote interest in the lesson among primary school students. Through a literature review, the article emphasizes the need for student-oriented teaching, gamification, and hands-on training to attract students and promote learning.